If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -8 = 5x + 5 Reorder the terms: -8 + 9x = 5x + 5 Reorder the terms: -8 + 9x = 5 + 5x Solving -8 + 9x = 5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -8 + 9x + -5x = 5 + 5x + -5x Combine like terms: 9x + -5x = 4x -8 + 4x = 5 + 5x + -5x Combine like terms: 5x + -5x = 0 -8 + 4x = 5 + 0 -8 + 4x = 5 Add '8' to each side of the equation. -8 + 8 + 4x = 5 + 8 Combine like terms: -8 + 8 = 0 0 + 4x = 5 + 8 4x = 5 + 8 Combine like terms: 5 + 8 = 13 4x = 13 Divide each side by '4'. x = 3.25 Simplifying x = 3.25
| 0.5*n(n-3)=54 | | -3x-17=-2 | | 8x-2+3x=13x+8 | | -11=x+16 | | 11w=3520 | | z-3=30 | | 10c=70 | | 5w+6=9w+3 | | q-6=6 | | 4=m-2 | | 12+g=16 | | t+15=19 | | sqrt(3x+2)=xsqrt(2) | | 12=((-3+1)(-3+1))(k) | | =x^4-6x^3+13*x^2-12*x+5 | | 0.5x(x-3)=54 | | x=2(6+2x)+8x | | 8x-20=2x-8 | | A=5*5*5(3.5) | | w+3/4=6 | | 3x+2=x^2-2 | | px^2-6x+p=0 | | 2x-36+x=90 | | 3x=2+5 | | 3j-9=6 | | 4x^2y-6xy^2=u | | 3x+x+2+4=18 | | x^2+x^2=c | | 9m-9=-45 | | x^2*X^2=c^2 | | C=(3C+5)+(4C-8) | | 12-x=4(x+13) |